Bibliometric Analysis of Research Dynamics of Circular Economy in Plastic Management - Judijanto, Loso; Firdayetti, Firdayetti (Westscience Press, 2025)
The circular economy has emerged as a transformative approach to addressing the global plastic waste crisis by emphasizing resource recovery, recycling, and sustainability. This study presents a bibliometric analysis of research dynamics in circular economy and plastic management, utilizing data exclusively from the Scopus database and analyzed with VOSviewer. Key findings reveal significant growth in research activity over the past two decades, with central themes such as